Gardasil® as adjunctive therapy for respiratory papillomatosis at Red Cross Children’s Hospital, Cape Town - Shavina Frank; Jessica K. McGuire; Fiona Kabagenyi; Vincent Pretorius; Shazia Peer (Journal of the Colleges of Medicine of South Africa)
Background: Juvenile onset recurrent respiratory papillomatosis (JoRRP) is an incurable condition caused by human papilloma virus (HPV) types 6 and 11, often requiring repeated surgeries and in severe cases, tracheostomy. This imposes a significant socioeconomic burden on patients and families. Gardasil®, a proven prophylactic HPV vaccine, is emerging as a potential adjuvant therapy. We studied its response on JoRRP patients at our center.